2019
DOI: 10.1186/s12879-019-4284-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C infection among the general population and high-risk groups in the EU/EEA: a systematic review update

Abstract: Background Although significant improvement in efficacy measured by a sustained virological response, the high acquisition costs of direct-acting antivirals limit the access for patients and influence the costs of healthcare resource utilisation in hepatitis C. It is important to have the latest estimates of prevalence, especially in high-risk groups, for cost of illness, cost-effectiveness and budget impact studies. Methods Original studies on the estimates of the prev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…The global estimated viremic HCV prevalence is around 1%, corresponding to a number of 71 million persons w it h p o s it ive HC V R NA worldwide. The mean prevalence in Europe is 0.65%, and Romania occupies the first place with 2.5% HCV prevalence, corresponding to 550,000 patients with positive viral loads [1,2]. Due to the asymptomatic character of the infection, most people (>80%) are unaware of HCV positivity, are not tested, diagnosed and treated on time, in this way spreading the virus and discovering their condition when in advanced stages of liver disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…The global estimated viremic HCV prevalence is around 1%, corresponding to a number of 71 million persons w it h p o s it ive HC V R NA worldwide. The mean prevalence in Europe is 0.65%, and Romania occupies the first place with 2.5% HCV prevalence, corresponding to 550,000 patients with positive viral loads [1,2]. Due to the asymptomatic character of the infection, most people (>80%) are unaware of HCV positivity, are not tested, diagnosed and treated on time, in this way spreading the virus and discovering their condition when in advanced stages of liver disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hepatitis C virus (HCV) infection is a worldwide public health problem with an estimated prevalence of 1% to 2% among the general population. 1 4 Research into viral replication mechanisms has identified potential therapeutic targets. 5 The development of new direct-acting antivirals (DAAs) against HCV was a great step forward in the treatment of this infection.…”
Section: Introductionmentioning
confidence: 99%
“…This rate is about 10-fold lower than the 6.7 cases per 100,000 inhabitants found in Brazil between 2001 and 2012, and 45-fold lower than the incidence rates found countrywide in 2017 (11.9 cases per 100,000 inhabitants) [33]. The incidence rates found in Brazil are much lower than in developed countries such as Canada and the United States and countries in Europe, which have much more developed and efficient screening and notification systems [34,35]. The reasons why the incidence levels were lower countrywide and worldwide than in the western region are not well established.…”
Section: Discussionmentioning
confidence: 82%